2019
DOI: 10.1103/physrevb.100.035134
|View full text |Cite
|
Sign up to set email alerts
|

SU(3) fermions on the honeycomb lattice at 13 filling

Abstract: SU(N ) symmetric fermions on a lattice, which can be realized in ultracold-atom-based quantum simulators, have very promising prospects for realizing exotic states of matter. Here we present the ground state phase diagram of the repulsive SU(3) Hubbard model on a honeycomb lattice at 1/3 filling obtained from infinite projected entangled pair states tensor network calculations. In the strongly interacting limit the ground state has plaquette order. Upon decreasing the interaction strength U/t we find a first o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Since the density of states at the Fermi energy diverges, Theorem 1 can be thought of as a result for a singular case. In order to establish a rigorous result for a nonsingular SU(n) Hubbard model, we consider the Hamiltonian (20). To state the theorem, let us define for Since the lowest band of Eq.…”
Section: Theorem 1 Consider the Su(n) Hubbard Hamiltonianmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the density of states at the Fermi energy diverges, Theorem 1 can be thought of as a result for a singular case. In order to establish a rigorous result for a nonsingular SU(n) Hubbard model, we consider the Hamiltonian (20). To state the theorem, let us define for Since the lowest band of Eq.…”
Section: Theorem 1 Consider the Su(n) Hubbard Hamiltonianmentioning
confidence: 99%
“…In this section, we shall prove Theorem 2. Here, we consider the model (20) with the fermion number N f = |E|. First, we rewrite the Hamiltonian H 2 as follows:…”
Section: Proof Of Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Besides the computation of ground states, for which (i)PEPS was originally developed, significant progress has also been achieved in other applications, including the study of thermodynamic properties [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], excited states [43,44], real-time evolution [36,[45][46][47] and open systems [36,48].…”
Section: Introductionmentioning
confidence: 99%
“…However, the recent experimental realizations of the SU(n) Hubbard models with ultracold fermionic atoms have generated renewed theoretical interest in the study of the model at finite n (> 2). A number of studies revealed that the models can exhibit exotic phases that do not appear in the SU(2) counterpart [13,14,15].…”
mentioning
confidence: 99%